Impact of Malls on Conventional Retail Formats - Small Shops and Hawkers: A Study of}ammu City - Jain, Deepak (Gyan Management Journal, 2011)
Retailing is the buzzword now-a-days and it is showing its presence and impact in a strong positive way. After reviewing thecurrentstatus of malls in different cities of India, authors studied the impact of Malls on small shops and hawkers within Jam mu City. Paper discusses the impact of malls on sales performances of hawkers and small retailers. A survey was conducted on 82 retailers and 30 hawkers engaged in different business near two malls present within Jammu city. Research shows that sales of later is reducing day-by-day because of malls. The decline in sales of hawkers and retail shops having business operations within groceries, fruits and vegetables, processed foods, garments, shoes, electronic and electrical goods categories, ultimately threatening 50 per cent of them with closure or a major decline in business.Only 10.7 per cent of the sample of small shops and hawkers so far been able to respond to the competitive threat of the malls with the institution of fresh sales promotion initiatives. There exists high degree of positive correlation between total number of shops & hawker's surveyed and total number of shops & hawkers showing sales decline i.e. 93.9%.
Keywords: Retail; Malls; Hawkers; Organized; Conventional and Shops